Composition for repairing tooth leukoplakia and preparation method thereof
By combining artificial saliva containing specific concentrations of phosphate, potassium ions and calcium ions with permeable resins, the problem of insufficient efficacy in treating tooth white spots is solved, and effective repair of tooth white spots with a long demineralization time or a heavier demineralization degree is achieved.
Patent Information
- Application Number
- CN202510144164.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-25
AI Technical Summary
When treating dental white spots, the efficacy of existing permeable resins is insufficient for dental white spots with a longer demineral time or a heavier demineralization degree, and their application is limited.
Artificial saliva containing specific concentrations of phosphate, potassium ions and calcium ions is used in combination with permeable resin to repair teeth white spots.
Through the use of this composition, the repair effect of leukoplakia can be significantly improved, especially in the case of a long demineral time or a heavy demineral degree, providing better chromatic aberration recovery and hardness improvement.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tooth restoration, and in particular, to a composition for repairing white spots on teeth and a preparation method thereof. Background Art
[0002] Normal tooth enamel usually appears transparent and has a uniform yellow-white color. However, due to plaque accumulation, demineralization caused by acidic foods, excessive fluoride intake during development, and trauma to deciduous teeth, chalky white patches, known as white spots, will form on the surface of the enamel.
[0003] The emerging material of infiltration resin is gradually being used to treat white spots on teeth. It enters the demineralized pores by siphoning, increasing the refractive index of the demineralized pores, visually masking the chalky appearance of white spots on teeth, and increasing the hardness of the demineralized enamel surface. Although infiltration resin can improve white spots to a certain extent, its efficacy still needs to be improved for white spots on teeth with a long demineralization time or a severe demineralization degree.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present application is to provide a composition for repairing white spots on teeth and a preparation method thereof, so as to solve at least one technical problem mentioned in the background technology.
[0006] Specifically, the first aspect of the present application provides a composition for repairing white spots on teeth, comprising the following components: Artificial saliva, Wherein, the artificial saliva comprises 0.2-1 g / L of dipotassium hydrogen phosphate and 0.2-1 g / L of calcium chloride.
[0007] By adopting the above technical scheme, artificial saliva containing specific concentrations of phosphate, potassium ions and calcium ions can be used in combination with the infiltration resin to achieve a good white spot repair effect on teeth, thereby solving the technical problem of limited application of infiltration resin under the existing technology.
[0008] Preferably, the artificial saliva comprises 0.6-0.8 g / L of dipotassium hydrogen phosphate and 0.3-0.4 g / L of calcium chloride.
[0009] Preferably, the artificial saliva further comprises inorganic salts, and the inorganic salts comprise one or a combination of the following components: Magnesium chloride 0.05-0.08g / L, Potassium chloride 0.5-2g / L, Sodium chloride 0.05-0.5 g / L; More preferably, the content of the inorganic salt is: Magnesium chloride 0.05-0.06g / L, Potassium chloride 1-1.5g / L, Sodium chloride 0.1-0.4g / L.
[0010] Preferably, the artificial saliva also includes 0.02-0.2 g / L of an antibacterial agent, wherein the antibacterial agent is selected from one or a combination of benzoic acid, sodium benzoate, sorbic acid, and potassium sorbate; more preferably, the content of the antibacterial agent is 0.04-0.1 g / L.
[0011] Preferably, the artificial saliva further comprises the following components: Povidone K30 0.01-0.2 g / L; Carboxymethyl cellulose 0.01-0.05g / L.
[0012] Preferably, the artificial saliva further comprises the following components: Povidone K30 0.05-0.1 g / L; Carboxymethyl cellulose 0.02-0.04g / L.
[0013] Preferably, the artificial saliva further comprises a pH regulator, and the pH regulator is selected from NaOH or HCl, and the content of both is not more than 0.1 g / L.
[0014] Preferably, the composition for repairing white spots on teeth further comprises an active glass composition, wherein every 100 parts by weight of the active glass composition comprises: Silicon dioxide (SiO2) 55-70 parts, Calcium oxide (CaO) 5-30 parts, Calcium difluoride (CaF2) 5-10 parts, Phosphorus pentoxide (P2O5) 3-7 parts, 3-5 parts of magnesium oxide (MgO), Barium oxide (BaO) 1-3 parts, Potassium oxide (K2O) 1-2 parts; The active glass composition is dissolved in water to form 5-10% active glass liquid.
[0015] Preferably, the particle size of the active glass composition is less than 50 μm.
[0016] In a second aspect of the present application, a kit is provided for repairing white spots on teeth, comprising the composition for repairing white spots on teeth as described in the first aspect of the present application.
[0017] Preferably, the kit further comprises a permeation resin.
[0018] Preferably, the kit also includes a demineralizing solution, which includes 80-120 mmol / L lactic acid, 15-20 mmol / L calcium chloride, and 6.0-8.0 mmol / L potassium dihydrogen phosphate.
[0019] The third aspect of the present application provides a method for preparing a composition for repairing white spots on teeth according to the first aspect of the present application, comprising the steps of: To prepare artificial saliva, take the indicated amount of potassium dihydrogen phosphate, calcium chloride, inorganic salt, and antibacterial agent, dissolve them in water and stir evenly; add povidone K30, stirring while adding until completely dissolved; add carboxymethyl cellulose, stirring while adding until completely dissolved; add NaOH or HCl to adjust the pH to 6.0-6.5.
[0020] Preferably, when preparing artificial saliva, the ambient temperature is controlled to be 25-35°C.
[0021] The fourth aspect of the present application provides a method for preparing a composition for repairing white spots on teeth as in the first aspect of the present application, comprising the steps of: To prepare artificial saliva, take the indicated amount of potassium dihydrogen phosphate, calcium chloride, inorganic salt, and antibacterial agent, dissolve them in water and stir evenly; add povidone K30, stirring while adding until completely dissolved; add carboxymethyl cellulose, stirring while adding until completely dissolved; add NaOH or HCl to adjust the pH to 6.0-6.5.
[0022] An active glass composition is prepared by melting the components of the active glass composition at 1000-1500° C. for 1-5 hours to melt and mix them; the mixture is quenched in deionized water at 0-4° C. to obtain a sintered active material raw material; and the sintered active material raw material is ground using a grinding device to a particle size of less than 50 μm.
[0023] Preferably, when preparing artificial saliva, the ambient temperature is controlled to be 25-35°C.
[0024] Preferably, the grinding device can be a ball mill.
[0025] Preferably, the active glass composition is added to deionized water to prepare a 5-10% solution.
[0026] In summary, this application has the following beneficial effects: First, the composition for repairing white spots on teeth provided in the present application can achieve good white spot repairing effects by using artificial saliva containing specific concentrations of phosphate, potassium ions, and calcium ions in combination with a penetrating resin, thereby solving the technical problem of limited application of penetrating resins in the prior art.
[0027] Second, the composition for repairing white spots on teeth provided in the present application, by combining artificial saliva with an active glass composition, can achieve technical effects such as better color restoration for white spots on teeth that have been demineralized for a long time or are severely demineralized.
[0028] Third, the preparation method of the composition for repairing white spots on teeth provided in the present application has a simple and effective process, a short production cycle, and low equipment requirements. The product prepared by this method has stable effect, good consistency, and has good application prospects. DETAILED DESCRIPTION
[0029] Here, exemplary embodiments will be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims.
[0030] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0031] The present application will be described in detail below through examples.
[0032] In the prior art, the emerging material of infiltration resin has been gradually applied to the treatment of white spots on teeth. It enters the demineralized pores by siphoning, increases the refractive index of the demineralized pores, visually masks the chalky appearance of white spots on teeth, and increases the surface hardness of demineralized enamel. Although infiltration resin can improve white spots to a certain extent, its efficacy still needs to be improved for white spots on teeth with a long demineralization time or a severe demineralization degree.
[0033] In view of this, in order to solve the existing technical problems in the background technology, the invention concept of this application is to provide a composition for repairing white spots on teeth, including components: infiltration resin; artificial saliva, wherein the artificial saliva includes 0.2-1g / L of dipotassium hydrogen phosphate and 0.2-1g / L of calcium chloride. According to this invention concept, by using artificial saliva containing specific concentrations of phosphate, potassium ions, and calcium ions, it can be combined with the infiltration resin to achieve a good white spot repair effect on teeth, thereby solving the technical problem of limited application of infiltration resin in the prior art.
[0034] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods. Those skilled in the art should also understand that the reaction time and drug feeding involved in this application cannot be absolutely accurate in the actual production process, but are all within the allowable error range. For example, if you expect to heat the sample for 30 minutes, the actual operation may be 1 second more or less than 1 second in 30 minutes; if you expect to weigh 30g of sample, you may actually weigh 30.001g or 29.998g.
[0035] The reagents used in this application are usually commercially available without any description. The specific sources of the reagents are listed as follows: Penetration resin: DMG-Icon penetration resin, purchased from DMG, Germany.
[0036] Gel acid etchant: Icon-hydrochloric acid gel acid etchant, purchased from DMG, Germany.
[0037] Desiccant: Icon-desiccant, purchased from DMG, Germany.
[0038] Acid-resistant nail polish: Lanxi Haiyan Cosmetics Co., Ltd.
[0039] Those skilled in the art should understand that the above reagents are only provided as a reference for the source of reagents and do not limit the scope of protection of the present application. Unless otherwise specified, the above reagents are not the only choice.
[0040] Experimental Example 1 Establishing tooth white spot model A
[0041] Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0042] The demineralization solution was prepared with 100mmol / L lactic acid, 18mmo1 / L calcium chloride, and 7.8mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 4.5. The samples were immersed in 50 ml of demineralization solution at 37°C for 25 days to produce chalky plaques on the tooth surface. The demineralization solution was replaced every day to obtain a crown white spot model.
[0043] Experimental Example 2 Establishing tooth white spot model B
[0044] This experimental example is basically the same as Experimental Example 1, except that: (1) Maintain the pH of the demineralized solution at 3.5; (2) Immerse the crown samples in demineralization solution for 50 days.
[0045] Experimental Example 3: Resin Infiltration Treatment
[0046] For the tooth crowns with white spots obtained in Experimental Examples 1 and 2, first use a rubber cup dipped in polishing paste to clean, rinse and blow dry, treat the tooth surface with Icon-hydrochloric acid gel etchant for 2 minutes, rinse for 30 seconds, completely remove the etching gel, and blow dry.
[0047] Then, Icon-Desiccant was used for 30 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 3 minutes, excess resin was removed, and light-cured for 40 seconds. Infiltration Resin was applied again, allowed to stand for 1 minute, excess resin was removed, and light-cured for 40 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0048] After treatment with infiltration resin, the white spots on the crowns will usually be visually improved to a certain extent. However, due to the limited penetration depth of the infiltration resin, white spots with severe demineralization still cannot be well treated. In this application, the crowns are remineralized to further repair the white spots on the teeth.
[0049] Experimental Example 4 Plaque Remineralization Experiment
[0050] The samples treated in Example 3 were subjected to remineralization treatment according to the following groups.
[0051] Group A:
[0052] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L; Add water to dissolve and stir evenly, then add NaOH or HCl to adjust the pH to 6.5.
[0053] Group B:
[0054] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L, add water to dissolve and stir evenly; Add povidone K30, stirring until it is completely dissolved, so that the content of povidone K30 is 0.1 g / L; Add NaOH or HCl to adjust the pH to 6.5.
[0055] Group C:
[0056] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L, add water to dissolve and stir evenly; Add carboxymethyl cellulose, stirring until it is completely dissolved, so that the carboxymethyl cellulose content is 0.04g / L; Add NaOH or HCl to adjust the pH to 6.5.
[0057] Group D:
[0058] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L, add water to dissolve and stir evenly; Add povidone K30, stirring until it is completely dissolved, so that the content of povidone K30 is 0.1 g / L; Add carboxymethyl cellulose, stirring until it is completely dissolved, so that the carboxymethyl cellulose content is 0.04g / L; Add NaOH or HCl to adjust the pH to 6.5.
[0059] Group E:
[0060] The present invention comprises artificial saliva and an active glass composition.
[0061] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L, add water to dissolve and stir evenly; Add povidone K30, stirring until it is completely dissolved, so that the content of povidone K30 is 0.1 g / L; Add carboxymethyl cellulose, stirring until it is completely dissolved, so that the carboxymethyl cellulose content is 0.04g / L; Add NaOH or HCl to adjust the pH to 6.5.
[0062] The active glass composition comprises, by weight, 64 / 100 parts of silicon dioxide, 20 / 100 parts of calcium oxide, 10 / 100 parts of calcium difluoride, 3 / 100 parts of phosphorus pentoxide, and 3 / 100 parts of magnesium oxide; The above components are melted at 1300° C. for 2 hours to be melted and mixed; the mixture is quenched in deionized water at 0° C. to obtain a sintered active material raw material; the sintered active material raw material is ground with a grinding device to a particle size of less than 50 μm; The active glass composition was dissolved in deionized water to form a 6% active glass solution.
[0063] Group F:
[0064] The present invention comprises artificial saliva and an active glass composition.
[0065] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L, add water to dissolve and stir evenly; Add povidone K30, stirring until it is completely dissolved, so that the content of povidone K30 is 0.1 g / L; Add carboxymethyl cellulose, stirring until it is completely dissolved, so that the carboxymethyl cellulose content is 0.04g / L; Add NaOH or HCl to adjust the pH to 6.5.
[0066] The active glass composition includes, by weight, 67 / 100 parts of silicon dioxide, 20 / 100 parts of calcium oxide, 10 / 100 parts of calcium difluoride, and 3 / 100 parts of phosphorus pentoxide.
[0067] The above components are melted at 1300° C. for 2 hours to be melted and mixed; the mixture is quenched in deionized water at 0° C. to obtain a sintered active material raw material; the sintered active material raw material is ground with a grinding device to a particle size of less than 50 μm; The active glass composition was dissolved in deionized water to form a 6% active glass solution.
[0068] Group G:
[0069] The present invention comprises artificial saliva and an active glass composition.
[0070] Artificial saliva, including: Dipotassium hydrogen phosphate 0.8g / L, calcium chloride 0.4g / L, magnesium chloride 0.06g / L, potassium chloride 1.5g / L, sodium chloride 0.4g / L, sodium benzoate 0.1g / L, add water to dissolve and stir evenly; Add povidone K30, stirring until it is completely dissolved, so that the content of povidone K30 is 0.1 g / L; Add carboxymethyl cellulose, stirring until it is completely dissolved, so that the carboxymethyl cellulose content is 0.04g / L; Add NaOH or HCl to adjust the pH to 6.5.
[0071] The active glass composition comprises, by weight, 60 / 100 parts of silicon dioxide, 20 / 100 parts of calcium oxide, 10 / 100 parts of calcium difluoride, 3 / 100 parts of phosphorus pentoxide, 3 / 100 parts of magnesium oxide, 2 / 100 parts of barium oxide, and 2 / 100 parts of potassium oxide.
[0072] The above components are melted at 1300° C. for 2 hours to be melted and mixed; the mixture is quenched in deionized water at 0° C. to obtain a sintered active material raw material; the sintered active material raw material is ground with a grinding device to a particle size of less than 50 μm; The active glass composition was dissolved in deionized water to form a 6% active glass solution.
[0073] Blank control group:
[0074] Deionized water.
[0075] For the AD group: the tooth crowns obtained in Experimental Example 1 and Experimental Example 2 were immersed in artificial saliva and stirred at 30 r / min for remineralization treatment for 30 days.
[0076] For the EG group: the tooth crowns obtained in Experimental Example 1 and Experimental Example 2 were immersed in artificial saliva and stirred at 30 r / min for remineralization for 30 days; during this period, the tooth crowns were taken out of the artificial saliva every 12 hours and immersed in 6% active glass solution for 5 minutes.
[0077] For the blank control group: the tooth crowns obtained in Experimental Example 1 and Experimental Example 2 were immersed in deionized water, stirred at 30 r / min, and then mineralized for 30 days.
[0078] Experimental Example 5: Vickers hardness test
[0079] Ten samples were randomly selected from each group before and 30 days after remineralization treatment. The HV of each sample was measured using a microhardness tester. Three points were randomly selected from the middle and lower parts of the test surface. The indenter load was adjusted to 100 g and pressed into the enamel surface for 15 seconds. The diagonal length of the indentation was measured under a microscope, and the HV value of the enamel surface was calculated. The average value was taken as the final HV.
[0080] Experimental Example 6: White spot color difference analysis
[0081] The crowns were photographed using a SLR digital camera, macro lens, and ring flash. The digital camera settings were as follows: shutter speed 1 / 60, F36, ISO100, automatic white balance. Digital photos were taken of the experimental group before remineralization treatment and 10 days, 20 days, and 30 days after treatment under the same conditions and environment.
[0082] Use image analysis software to select all white spots on the tooth surface and obtain the average values of the white spot color index L, a, and b. Use the color difference formula (ΔE=[(ΔL) 2 + (Δa) 2 +(Δb) 2 ] 1 / 2 ) to calculate the color difference value.
[0083] Experimental Example 7
[0084] Using the methods of Experimental Examples 5 and 6, hardness analysis and white spot color difference analysis were performed on each group in Experimental Example 4. The experimental results are shown in Tables 1-4.
[0085] Among them, the Vickers hardness test results of each group in Experimental Example 4 after being applied to the crown of Experimental Example 1 are shown in Table 1.
[0086] Table 1 Vickers hardness test results of each group in Experimental Example 4 after being applied to the crown of Experimental Example 1 Group Before remineralization After remineralization Is the p-value less than 0.05? Group A 325±5 386±5 yes Group B 318±6 392±5 yes Group C 320±6 395±6 yes Group D 316±7 398±5 yes Group E 326±5 396±7 yes Group F 320±7 393±5 yes Group G 313±6 405±7 yes Blank control group 322±6 323±5 no The Vickers hardness test results of each group in Experimental Example 4 after being applied to the crown of Experimental Example 2 are shown in Table 2.
[0087] Table 2 Vickers hardness test results of each group in Experimental Example 4 after being applied to the crown of Experimental Example 2 Group Before remineralization After remineralization Is the P value less than 0.05? Group A 283±4 302±5 yes Group B 286±5 306±5 yes Group C 286±6 310±4 yes Group D 293±6 343±6 yes Group E 288±4 349±6 yes Group F 290±5 356±5 yes Group G 285±5 355±5 yes Blank control group 291±6 293±4 no According to the data in Table 1-Table 2, those skilled in the art can preliminarily draw the following conclusions: First, as shown in Tables 1 and 2, after the remineralization schemes of Groups A to G were applied to the crowns treated in Experimental Example 1, the Vickers hardness was significantly improved, indicating that the artificial saliva proposed in this application has a good remineralization effect; Second, as shown in Table 2, the increase in Vickers hardness of Group A-C after being applied to the crowns treated in Experimental Example 2 was significantly lower than that in Experimental Example 1, which indicates that the Group A-C scheme did not restore the hardness well after remineralization for crowns with a longer demineralization time.
[0088] Third, as shown in Table 2, the crowns of groups D-G had higher Vickers hardness after remineralization than those of groups A-C, and the calculated p values were all less than 0.05. This indicates that the artificial saliva of group D has a better hardness recovery effect on teeth with a longer demineralization time.
[0089] The experimental results of the white spot color difference analysis of each group in Experimental Example 4 after being applied to the crown of Experimental Example 1 are shown in Table 3.
[0090] Table 3 Experimental results of color difference analysis of white spots after each group in Experimental Example 4 was applied to the crown of Experimental Example 1 Group ΔE (10 days) ΔE (20 days) ΔE (30 days) Group A 1.5±0.2 1.8±0.1 1.9±0.2 Group B 1.4±0.1 1.8±0.2 2.1±0.2 Group C 1.5±0.2 1.7±0.1 1.9±0.1 Group D 1.8±0.2 2.0±0.1 2.3±0.1 Group E 2.0±0.2 2.4±0.1 2.6±0.2 Group F 1.8±0.1 2.2±0.2 2.5±0.1 Group G 2.5±0.2 3.0±0.2 3.3±0.1 Blank control group Less than 0.1 Less than 0.1 Less than 0.1 The experimental results of the white spot color difference analysis after each group in Experimental Example 4 was applied to the crown of Experimental Example 2 are shown in Table 4.
[0091] Table 4 The results of the color difference analysis of white spots after each group in Experimental Example 4 was applied to the crown of Experimental Example 2 Group ΔE (10 days) ΔE (20 days) ΔE (30 days) Group A 0.8±0.1 1.0±0.1 1.1±0.1 Group B 0.7±0.1 0.9±0.1 1.1±0.1 Group C 0.8±0.1 1.1±0.1 1.3±0.1 Group D 0.8±0.1 1.2±0.1 1.3±0.1 Group E 1.0±0.1 1.3±0.1 1.6±0.1 Group F 0.9±0.1 1.3±0.1 1.5±0.1 Group G 2.2±0.1 2.8±0.2 3.1±0.1 Blank control group Less than 0.1 Less than 0.1 Less than 0.1 According to the data in Table 3-Table 4, those skilled in the art can preliminarily draw the following conclusions: First, as shown in Tables 3 and 4, after the remineralization schemes of Groups A to G were applied to the crowns treated in Experimental Example 1, the color difference of white spots was significantly improved, indicating that the artificial saliva proposed in this application has a good remineralization effect; Second, as shown in Table 4, the degree of improvement in color difference after Group A-Group F was applied to the crowns treated in Experimental Example 2 was significantly lower than that in Experimental Example 1, which indicates that the treatment of Group A-Group F is not effective in restoring color difference after remineralization for crowns with a longer demineralization time.
[0092] Third, as shown in Table 4, the color difference restoration of the crown after remineralization in Group G was significantly better than that in Groups A-F, and the calculated p values were all less than 0.05. This shows that the active glass composition of Group G has a better color difference restoration effect for teeth with a longer demineralization time.
[0093] Example 1 S1 Crown white spot model construction: Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0094] The demineralization solution was prepared with 80mmol / L lactic acid, 15mmo1 / L calcium chloride, and 6.0mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 3.5. The samples were immersed in 50 ml of the demineralization solution at 37°C for 50 days to produce chalky plaques on the tooth surface, and the demineralization solution was replaced every day.
[0095] S2 Resin infiltration treatment: The crown with white spots obtained in the previous step was first cleaned with a rubber cup dipped in polishing paste, rinsed and blown dry, and the tooth surface was treated with Icon-hydrochloric acid gel etchant for 1 min, rinsed for 60 s, the etching gel was completely removed, and blown dry.
[0096] Then, Icon-Desiccant was used for 20 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 2 minutes, excess resin was removed, and light-cured for 30 seconds. Infiltration Resin was applied again, allowed to stand for 0.5 minutes, excess resin was removed, and light-cured for 30 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0097] S3 Remineralization treatment: The tooth crown obtained in step S2 was immersed in artificial saliva and stirred at 20 r / min for remineralization treatment for 30 days.
[0098] Wherein, the preparation method of the artificial saliva comprises: Dipotassium hydrogen phosphate 0.6g / L, calcium chloride 0.2g / L, magnesium chloride 0.05g / L, potassium chloride 1g / L, sodium chloride 0.1g / L, sodium benzoate 0.04g / L, povidone K30 0.05g / L, carboxymethyl cellulose 0.02g / L. Take the above components, dissolve them in water at 25℃ and stir evenly; add NaOH or HCl to adjust the pH to 6.0.
[0099] Example 2 S1 Crown white spot model construction: Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0100] The demineralization solution was prepared with 100mmol / L lactic acid, 18mmo1 / L calcium chloride, and 7.8mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 3.5. The samples were immersed in 50 ml of the demineralization solution at 37°C for 50 days to produce chalky plaques on the tooth surface, and the demineralization solution was replaced every day.
[0101] S2 Resin infiltration treatment: The crown with white spots obtained in the previous step was first cleaned with a rubber cup dipped in polishing paste, rinsed and blown dry, and the tooth surface was treated with Icon-hydrochloric acid gel etchant for 2 minutes, rinsed for 30 seconds, the etching gel was completely removed, and blown dry.
[0102] Then, Icon-Desiccant was used for 30 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 3 minutes, excess resin was removed, and light-cured for 40 seconds. Infiltration Resin was applied again, allowed to stand for 1 minute, excess resin was removed, and light-cured for 40 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0103] S3 Remineralization treatment: The tooth crown obtained in step S2 was immersed in artificial saliva and stirred at 30 r / min for remineralization treatment for 30 days.
[0104] Wherein, the preparation method of the artificial saliva comprises: Dipotassium hydrogen phosphate 0.8 g / L, calcium chloride 0.4 g / L, magnesium chloride 0.06 g / L, potassium chloride 1.5 g / L, sodium chloride 0.4 g / L, sodium benzoate 0.1 g / L, povidone K30 0.1 g / L, carboxymethyl cellulose 0.04 g / L. Take the above components, dissolve them in water at 30°C and stir evenly; add NaOH or HCl to adjust the pH to 6.5.
[0105] Example 3 S1 Crown white spot model construction: Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0106] The demineralization solution was prepared with 120mmol / L lactic acid, 20mmo1 / L calcium chloride, and 8.0mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 3.5. The samples were immersed in 50 ml of the demineralization solution at 37°C for 50 days to produce chalky plaques on the tooth surface, and the demineralization solution was replaced every day.
[0107] S2 Resin infiltration treatment: The crown with white spots obtained in the previous step was first cleaned with a rubber cup dipped in polishing paste, rinsed and blown dry, and the tooth surface was treated with Icon-hydrochloric acid gel etchant for 3 minutes, rinsed for 20 seconds, the etching gel was completely removed, and blown dry.
[0108] Then, Icon-Desiccant was used for 40 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 4 minutes, excess resin was removed, and light-cured for 50 seconds. Infiltration Resin was applied again, allowed to stand for 2 minutes, excess resin was removed, and light-cured for 50 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0109] S3 Remineralization treatment: The tooth crown obtained in step S2 was immersed in artificial saliva and stirred at 35 r / min for remineralization treatment for 30 days.
[0110] Wherein, the preparation method of the artificial saliva comprises: Dipotassium hydrogen phosphate 1g / L, calcium chloride 1g / L, magnesium chloride 0.08g / L, potassium chloride 1.5g / L, sodium chloride 0.2g / L, sodium benzoate 0.2g / L, povidone K30 0.2g / L, carboxymethyl cellulose 0.05g / L. Take the above components, dissolve them in water at 35℃ and stir evenly; add NaOH or HCl to adjust the pH to 6.5.
[0111] Example 4 This embodiment is basically the same as embodiment 1, except that the preparation method of artificial saliva is: Wherein, the preparation method of the artificial saliva comprises: At an ambient temperature of 25°C, weigh 0.6 g / L of dipotassium hydrogen phosphate, 0.2 g / L of calcium chloride, 0.05 g / L of magnesium chloride, 1 g / L of potassium chloride, 0.1 g / L of sodium chloride, and 0.04 g / L of sodium benzoate, add water to dissolve and stir evenly; add povidone K30 while stirring until it is completely dissolved, so that the content of povidone K30 is 0.05 g / L; add carboxymethyl cellulose while stirring until it is completely dissolved, so that the content of carboxymethyl cellulose is 0.02 g / L; add NaOH or HCl to adjust the pH to 6.0.
[0112] Example 5 This embodiment is basically the same as embodiment 2, except that the preparation method of artificial saliva is: Wherein, the preparation method of the artificial saliva comprises: At an ambient temperature of 30°C, weigh 0.8 g / L of dipotassium hydrogen phosphate, 0.4 g / L of calcium chloride, 0.06 g / L of magnesium chloride, 1.5 g / L of potassium chloride, 0.4 g / L of sodium chloride, and 0.1 g / L of sodium benzoate, add water to dissolve and stir evenly; add povidone K30 while stirring until it is completely dissolved, so that the content of povidone K30 is 0.1 g / L; add carboxymethyl cellulose while stirring until it is completely dissolved, so that the content of carboxymethyl cellulose is 0.04 g / L; add NaOH or HCl to adjust the pH to 6.5.
[0113] Example 6 This embodiment is basically the same as embodiment 3, except that the preparation method of artificial saliva is: Wherein, the preparation method of the artificial saliva comprises: At an ambient temperature of 35°C, weigh 1 g / L of potassium dihydrogen phosphate, 1 g / L of calcium chloride, 0.08 g / L of magnesium chloride, 1.5 g / L of potassium chloride, 0.2 g / L of sodium chloride, and 0.2 g / L of sodium benzoate, add water to dissolve and stir evenly; add povidone K30 while stirring until it is completely dissolved, so that the content of povidone K30 is 0.2 g / L; add carboxymethyl cellulose while stirring until it is completely dissolved, so that the content of carboxymethyl cellulose is 0.05 g / L; add NaOH or HCl to adjust the pH to 6.5.
[0114] Example 7 S1 Crown white spot model construction: Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0115] The demineralization solution was prepared with 80mmol / L lactic acid, 15mmo1 / L calcium chloride, and 6.0mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 3.5. The samples were immersed in 50 ml of the demineralization solution at 37°C for 50 days to produce chalky plaques on the tooth surface, and the demineralization solution was replaced every day.
[0116] S2 Resin infiltration treatment: The crown with white spots obtained in the previous step was first cleaned with a rubber cup dipped in polishing paste, rinsed and blown dry, and the tooth surface was treated with Icon-hydrochloric acid gel etchant for 1 min, rinsed for 60 s, the etching gel was completely removed, and blown dry.
[0117] Then, Icon-Desiccant was used for 20 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 2 minutes, excess resin was removed, and light-cured for 30 seconds. Infiltration Resin was applied again, allowed to stand for 0.5 minutes, excess resin was removed, and light-cured for 30 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0118] S3 Remineralization treatment: The tooth crowns obtained in step S2 were immersed in artificial saliva and stirred at 20 r / min for 30 days. During this period, the tooth crowns were taken out from the artificial saliva every 12 hours and immersed in 5% active glass liquid for 10 minutes.
[0119] The preparation method of artificial saliva comprises: at an ambient temperature of 25°C, weighing 0.6 g / L of dipotassium hydrogen phosphate, 0.2 g / L of calcium chloride, 0.05 g / L of magnesium chloride, 1 g / L of potassium chloride, 0.1 g / L of sodium chloride, and 0.04 g / L of sodium benzoate, adding water to dissolve and stirring evenly; adding povidone K30, stirring while adding until completely dissolved, so that the content of povidone K30 is 0.05 g / L; adding carboxymethyl cellulose, stirring while adding until completely dissolved, so that the content of carboxymethyl cellulose is 0.02 g / L; and adding NaOH or HCl to adjust the pH to 6.0.
[0120] The preparation method of active glass liquid includes: preparing an active glass composition, which includes 55 / 100 parts of silicon dioxide, 30 / 100 parts of calcium oxide, 5 / 100 parts of calcium difluoride, 3 / 100 parts of phosphorus pentoxide, 5 / 100 parts of magnesium oxide, 1 / 100 parts of barium oxide, and 1 / 100 parts of potassium oxide by weight. Melting the above components at 1000°C for 5 hours to melt and mix them; placing the mixture in deionized water at 4°C for quenching to obtain a sintered active material raw material; grinding the sintered active material raw material with a grinding device to a particle size of less than 50μm; and dissolving the active glass composition in deionized water to form a 5% active glass liquid.
[0121] Example 8 S1 Crown white spot model construction: Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0122] The demineralization solution was prepared with 100mmol / L lactic acid, 18mmo1 / L calcium chloride, and 7.8mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 3.5. The samples were immersed in 50 ml of the demineralization solution at 37°C for 50 days to produce chalky plaques on the tooth surface, and the demineralization solution was replaced every day.
[0123] S2 Resin infiltration treatment: The crown with white spots obtained in the previous step was first cleaned with a rubber cup dipped in polishing paste, rinsed and blown dry, and the tooth surface was treated with Icon-hydrochloric acid gel etchant for 2 minutes, rinsed for 30 seconds, the etching gel was completely removed, and blown dry.
[0124] Then, Icon-Desiccant was used for 30 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 3 minutes, excess resin was removed, and light-cured for 40 seconds. Infiltration Resin was applied again, allowed to stand for 1 minute, excess resin was removed, and light-cured for 40 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0125] S3 Remineralization treatment: The tooth crown obtained in step S2 was immersed in artificial saliva and stirred at 30 r / min for remineralization treatment for 30 days.
[0126] The method for preparing artificial saliva comprises: weighing 0.8 g / L of dipotassium hydrogen phosphate, 0.4 g / L of calcium chloride, 0.06 g / L of magnesium chloride, 1.5 g / L of potassium chloride, 0.4 g / L of sodium chloride, 0.1 g / L of sodium benzoate, 0.1 g / L of povidone K30, and 0.04 g / L of carboxymethyl cellulose at an ambient temperature of 30°C, dissolving the above components in water and stirring evenly; and adding NaOH or HCl to adjust the pH to 6.5.
[0127] The preparation method of the active glass liquid comprises: preparing an active glass composition, which comprises, by weight, 60 / 100 parts of silicon dioxide, 20 / 100 parts of calcium oxide, 10 / 100 parts of calcium difluoride, 3 / 100 parts of phosphorus pentoxide, 3 / 100 parts of magnesium oxide, 2 / 100 parts of barium oxide, and 2 / 100 parts of potassium oxide. Melting the above components at 1300° C. for 2 hours to melt and mix them; placing the mixture in deionized water at 0° C. to quench and obtain a sintered active material raw material; grinding the sintered active material raw material with a grinding device to a particle size of less than 50 μm; and dissolving the active glass composition in deionized water to form a 6% active glass liquid.
[0128] Example 9 S1 Crown white spot model construction: Use a sandpaper to cut perpendicularly to the long axis of the isolated tooth and horizontally along the cementoenamel junction to obtain the crown part. Then use a high-speed bur to cut along the line connecting the labial and lingual surfaces of the crown, clean the cavity, and evenly apply transparent acid-resistant nail polish to all cut surfaces, and polish the enamel surface with sandpaper.
[0129] The demineralization solution was prepared with 120mmol / L lactic acid, 20mmo1 / L calcium chloride, and 8.0mmol / L potassium dihydrogen phosphate, and potassium hydroxide was used to maintain the pH at 3.5. The samples were immersed in 50 ml of the demineralization solution at 37°C for 50 days to produce chalky plaques on the tooth surface, and the demineralization solution was replaced every day.
[0130] S2 Resin infiltration treatment: The crown with white spots obtained in the previous step was first cleaned with a rubber cup dipped in polishing paste, rinsed and blown dry, and the tooth surface was treated with Icon-hydrochloric acid gel etchant for 3 minutes, rinsed for 20 seconds, the etching gel was completely removed, and blown dry.
[0131] Then, Icon-Desiccant was used for 40 seconds. Finally, Icon-Infiltration Resin was applied, allowed to stand for 4 minutes, excess resin was removed, and light-cured for 50 seconds. Infiltration Resin was applied again, allowed to stand for 2 minutes, excess resin was removed, and light-cured for 50 seconds. Fine polishing was performed, and the surface was immersed in distilled water for 1 week to restore the dehydrated state.
[0132] S3 Remineralization treatment: The tooth crown obtained in step S2 was immersed in artificial saliva and stirred at 35 r / min for remineralization treatment for 30 days.
[0133] The method for preparing artificial saliva comprises: weighing 1 g / L of dipotassium hydrogen phosphate, 1 g / L of calcium chloride, 0.08 g / L of magnesium chloride, 1.5 g / L of potassium chloride, 0.2 g / L of sodium chloride, 0.2 g / L of sodium benzoate, 0.2 g / L of povidone K30, and 0.05 g / L of carboxymethyl cellulose at an ambient temperature of 35°C, dissolving the above components in water and stirring evenly; and adding NaOH or HCl to adjust the pH to 6.5.
[0134] The preparation method of the active glass liquid comprises: preparing an active glass composition, which comprises, by weight, 70 / 100 parts of silicon dioxide, 5 / 100 parts of calcium oxide, 10 / 100 parts of calcium difluoride, 7 / 100 parts of phosphorus pentoxide, 3 / 100 parts of magnesium oxide, 3 / 100 parts of barium oxide, and 2 / 100 parts of potassium oxide. Melting the above components at 1500° C. for 1 hour to melt and mix them; placing the mixture in deionized water at 0° C. to quench and obtain a sintered active material raw material; grinding the sintered active material raw material with a grinding device to a particle size of less than 50 μm; and dissolving the active glass composition in deionized water to form a 10% active glass liquid.
[0135] Comparative Example 1 This comparative example is substantially the same as Example 8, except that: The active glass composition is ground to 100 μm-200 μm and then dissolved in deionized water.
[0136] Comparative Example 2 This comparative example is substantially the same as Example 8, except that: Disodium oxide (Na2O) is added to the active glass composition, so that the active glass composition comprises, by weight: 60 / 110 parts of silicon dioxide, 20 / 110 parts of calcium oxide, 10 / 110 parts of calcium difluoride, 3 / 110 parts of phosphorus pentoxide, 3 / 110 parts of magnesium oxide, 2 / 110 parts of barium oxide, 2 / 110 parts of dipotassium oxide, and 10 / 100 parts of disodium oxide.
[0137] Comparative Example 3 This comparative example is substantially the same as Example 5, except that: The pH of artificial saliva was adjusted to 5.5 using NaOH or HCl.
[0138] Comparative Example 4 Blank Control Group This comparative example is substantially the same as Example 5, except that: In the remineralization treatment step S3, the tooth crown obtained in step S2 is immersed in deionized water and stirred at 30 r / min for 30 days.
[0139] The tooth crowns with white spots treated according to the methods of Examples 1-9 and Comparative Examples 1-3 were tested for their Vickers hardness and white spot color difference using the methods of Experimental Examples 5-6. The test results are shown in Tables 5-6.
[0140] Among them, the Vickers hardness test results of the crowns in Examples 1-9 and Comparative Examples 1-3 are shown in Table 5.
[0141] Table 5 Vickers hardness test results of crowns in Examples 1-9 and Comparative Examples 1-3 Group Before remineralization After remineralization Is the p-value less than 0.05? Example 1 286±6 322±6 yes Example 2 290±5 318±6 yes Example 3 292±7 320±5 yes Example 4 287±6 332±5 yes Example 5 293±6 343±6 yes Example 6 282±5 340±5 yes Example 7 291±6 342±6 yes Example 8 285±5 355±5 yes Example 9 288±6 357±4 yes Comparative Example 1 285±4 350±6 yes Comparative Example 2 294±6 345±5 yes Comparative Example 3 296±5 328±5 yes Blank control group 291±6 293±4 no According to the data in Table 5, those skilled in the art can preliminarily draw the following conclusions: First, as shown in Table 5, after being treated with the remineralization schemes of Examples 1-9, the Vickers hardness of the crowns was significantly improved, indicating that the artificial saliva proposed in this application has a good remineralization effect; Second, compared with Example 5, the Vickers hardness of Comparative Example 3 after remineralization is lower, and the difference between the two data after calculation is significant (p is less than 0.05); this shows that the pH range of artificial saliva will have a more obvious effect on its remineralization effect; Third, compared with Examples 4-6, the Vickers hardness of Examples 1-3 after remineralization is lower, and the data differences between the two are significant after calculation (p is less than 0.05); the applicant speculates that in the preparation process of artificial saliva, dissolving povidone K30 and carboxymethyl cellulose in sequence according to the method of this embodiment can make the dissolution uniformity of the components of artificial saliva better, avoiding problems such as precipitation or insufficient dissolution.
[0142] The experimental results of color difference analysis of white spots on the crowns of Examples 1-9 and Comparative Examples 1-3 are shown in Table 6.
[0143] Table 6 Experimental results of color difference analysis of white spots on crowns in Examples 1-9 and Comparative Examples 1-3 Group ΔE (10 days) ΔE (20 days) ΔE (30 days) Example 1 0.7±0.1 0.9±0.1 1.1±0.1 Example 2 0.7±0.1 1.0±0.1 1.1±0.1 Example 3 0.8±0.1 1.1±0.1 1.2±0.1 Example 4 0.7±0.1 1.1±0.1 1.2±0.1 Example 5 0.8±0.1 1.2±0.1 1.3±0.1 Example 6 0.8±0.1 1.1±0.1 1.3±0.1 Example 7 2.1±0.1 2.6±0.2 3.0±0.1 Example 8 2.2±0.1 2.8±0.2 3.1±0.1 Example 9 2.2±0.1 2.9±0.1 3.4±0.2 Comparative Example 1 1.4±0.1 1.9±0.2 2.1±0.1 Comparative Example 2 1.8±0.1 2.3±0.1 2.6±0.2 Comparative Example 3 0.4±0.1 0.7±0.1 0.8±0.1 Blank control group Less than 0.1 Less than 0.1 Less than 0.1 According to the data in Table 6, those skilled in the art can preliminarily draw the following conclusions: First, as shown in Table 6, after being treated with the remineralization schemes of Examples 1-9, the color difference of the white spots on the crowns of the teeth was significantly improved, indicating that the artificial saliva proposed in this application has a good remineralization effect; Second, compared with Example 8, the improvement effect of white spot color difference after remineralization in Comparative Example 1 is poor, and the difference between the two data after calculation is significant (p is less than 0.05); this shows that the active glass composition, especially its particle size, has a more obvious effect on its remineralization effect; Third, compared with Example 8, the improvement effect of white spot color difference after remineralization in Comparative Example 2 is poor, and the difference between the two data after calculation is significant (p is less than 0.05); this shows that the addition of other metal oxide components to the active glass composition is likely to affect the properties of the active glass composition, thereby affecting the remineralization effect of the solution; Fourth, compared with Examples 7-9, the improvement effect of the color difference of white spots after remineralization in Examples 4-6 is poor, which once again confirms the technical effect that the combination of artificial saliva and active glass composition in the present application can have a better effect on white spots on teeth with a long demineralization time.
[0144] Therefore, more specifically, the composition for repairing white spots on teeth and the preparation method thereof provided in the embodiments of the present invention are particularly applicable to the repair of white spots on tooth crowns.
[0145] In summary, the composition for repairing white spots on teeth and the preparation method thereof provided in the embodiments of the present invention can achieve good white spot repairing effects by using artificial saliva containing specific concentrations of phosphate, potassium ions and calcium ions in combination with a penetration resin, thereby solving the technical problem of limited application of penetration resins in the prior art and having good application prospects.
[0146] It should be pointed out that for ordinary technicians in this field, the technical features in the above embodiments can be freely combined, and the formed technical solutions also belong to the embodiments disclosed in this application.
[0147] Furthermore, without departing from the principles of the present application, several improvements and modifications may be made to the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.
Claims
1. A composition for repairing white spots on teeth, characterized in that: Including components: Artificial saliva, Wherein, the artificial saliva comprises 0.2-1 g / L of dipotassium hydrogen phosphate and 0.2-1 g / L of calcium chloride.
2. The composition for repairing white spots on teeth according to claim 1, characterized in that: The artificial saliva also includes inorganic salts, which include one or a combination of the following components: Magnesium chloride 0.05-0.08g / L, Potassium chloride 0.5-2g / L, Sodium chloride 0.05-0.5g / L.
3. The composition for repairing white spots on teeth according to claim 1, characterized in that: The artificial saliva also includes 0.02-0.2 g / L of an antibacterial agent, wherein the antibacterial agent is selected from one or a combination of benzoic acid, sodium benzoate, sorbic acid, and potassium sorbate.
4. The composition for repairing white spots on teeth according to claim 1, characterized in that: The artificial saliva also includes components: Povidone K30 0.01-0.2 g / L; Carboxymethyl cellulose 0.01-0.05g / L.
5. The composition for repairing white spots on teeth according to any one of claims 1 to 4, characterized in that: The composition for repairing white spots on teeth further comprises an active glass composition, wherein every 100 parts by weight of the active glass composition comprises: 55-70 parts of silicon dioxide, Calcium oxide 5-30 parts, Calcium difluoride 5-10 parts, 3-7 parts of phosphorus pentoxide, 3-5 parts of magnesium oxide, 1-3 parts of barium oxide, 1-2 parts of potassium oxide; The active glass composition is dissolved in water to form 5-10% active glass liquid.
6. A kit, characterized in that: Used for repairing white spots on teeth, comprising the composition for repairing white spots on teeth as described in any one of claims 1 to 5.
7. The kit according to claim 6, characterized in that: The kit also includes a permeation resin.
8. The kit according to claim 6 or 7, characterized in that: The kit also includes a demineralizing solution, which includes 80-120 mmol / L lactic acid, 15-20 mmol / L calcium chloride, and 6.0-8.0 mmol / L potassium dihydrogen phosphate.
9. A method for preparing the composition for repairing white spots on teeth according to any one of claims 1 to 4, characterized in that: Includes steps: To prepare artificial saliva, take the indicated amount of potassium dihydrogen phosphate, calcium chloride, inorganic salt, and antibacterial agent, dissolve them in water and stir evenly; add povidone K30, stirring while adding until completely dissolved; add carboxymethyl cellulose, stirring while adding until completely dissolved; add NaOH or HCl to adjust the pH to 6.0-6.
5.
10. A method for preparing the composition for repairing white spots on teeth as claimed in claim 5, characterized in that: Includes steps: To prepare artificial saliva, take the indicated amount of potassium dihydrogen phosphate, calcium chloride, inorganic salt, and antibacterial agent, add water to dissolve and stir evenly; add povidone K30, stirring while adding until completely dissolved; add carboxymethyl cellulose, stirring while adding until completely dissolved; add NaOH or HCl to adjust the pH to 6.0-6.5; An active glass composition is prepared by melting the components of the active glass composition at 1000-1500° C. for 1-5 hours to melt and mix them; the mixture is quenched in deionized water at 0-4° C. to obtain a sintered active material raw material; and the sintered active material raw material is ground using a grinding device to a particle size of less than 50 μm.
Citation Information
Patent Citations
Tooth remineralisation
CN102245153A
Composition realizing remineralization of enamel
CN108403444A
Tooth desensitizer containing phosphosilicate glass as well as preparation method and application thereof
CN108618967A
Artificial saliva and its preparing method
CN1130066A
Tooth mineralization antibacterial bifunctional gel as well as preparation method and application thereof
CN115957237A